m7G Methyltransferase METTL1 Promotes Post-ischemic Angiogenesis via Promoting VEGFA mRNA Translation - Zhao, Yongchao; Kong, Lingqiu; Pei, Zhiqiang; Li, Fuhai; Li, Chaofu; Sun, Xiaolei; Shi, Bei; Ge, Junbo (Frontiers in Cell and Developmental Biology, 2021)
Post-transcriptional modifications play pivotal roles in various pathological processes and ischemic disorders. However, the role of N7-methylguanosine (m7G), particularly m7G in mRNA, on post-ischemic angiogenesis remains largely unknown. Here, we identified that methyltransferase like 1 (METTL1) was a critical candidate responsible for a global decrease of m7G within mRNA from the ischemic tissues. The in vivo gene transfer of METTL1 improved blood flow recovery and increased angiogenesis with enhanced mRNA m7G upon post-ischemic injury. Increased METTL1 expression using plasmid transfection in vitro promoted HUVECs proliferation, migration, and tube formation with a global increase of m7G in mRNA. Mechanistically, METTL1 promoted VEGFA mRNA translation in an m7G methylation-dependent manner. Our findings emphasize a critical link between mRNA m7G and ischemia and provide a novel insight of targeting METTL1 in the therapeutic angiogenesis for ischemic disorders, including peripheral arterial disease.